(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The purpose of this study is to explore the relationship between perceived organizational support (POS) and work engagement of administrative staff in newly-established universities of China. For this purpose, this article reviewed related literature and theories, proposed a single hypothesis. Primary data was collected by the self-administrated questionnaire which included 2 scales and 33 items. The findings showed that there was a positive relationship between POS and work engagement, and also illustrated that POS was the predictor of work engagement. In view of the low level of POS determined by study survey, it was suggested that newly-established university should improve administrative staff’s work engagement by concerning their POS.